Pengaruh Informasi Arus Kas terhadap Return Saham Perusahaan Studi Kasus Pada Perusahaan Yang Tercatat Di Bei Pada Indeks LQ45 - Kurtubi, Ahmad; Pramiudi, Udi (Jurnal Ilmiah Akuntansi Kesatuan, 2014)
The purpose of this study was to determine the cash flow information , stock returns , as well as to determine the effect of cash flow information on stock returns , the company entered in the LQ’45 group , by looking at the share price a week before and a week after the financial statements published. Methods This study uses descriptive method , namely decipher cash flow information and stock returns and cash flow of information influence on stock returns in LQ’45 companies.The results showed the average of total cash flow who increased in LQ’45 Companies group , and stock returns has increased as well , the cash flow of information has influence on stock returns after reporting cash flow published for three consecutive years